2018
DOI: 10.3390/fermentation4010006
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Biogenic Amines in Wine: Role of Alcoholic and Malolactic Fermentation

Abstract: Biogenic amines (BAs) are detrimental to health and originate in foods mainly from decarboxylation of the corresponding amino acid by the activity of exogenous enzymes released by various microorganisms. BAs can be generated at different stages of the wine production. Some of them are formed in the vineyard and are normal constituents of grapes with amounts varying with variety, soil type and composition, fertilization and climatic conditions during growth and degree of maturation. BAs can be also formed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 90 publications
1
35
0
Order By: Relevance
“…Extended lees contact also seems to be responsible for higher BAs concentrations in wines [55]. LABs present in wines can hydrolyze and decarboxylate higher levels of peptides and free amino acids released by yeasts [62]. However, in our data there were no significant modification of any of the amines after the five months of wine storage, and no amines other than those found at the end of the MLF were detected (Table 4).…”
Section: Biogenic Aminesmentioning
confidence: 42%
See 1 more Smart Citation
“…Extended lees contact also seems to be responsible for higher BAs concentrations in wines [55]. LABs present in wines can hydrolyze and decarboxylate higher levels of peptides and free amino acids released by yeasts [62]. However, in our data there were no significant modification of any of the amines after the five months of wine storage, and no amines other than those found at the end of the MLF were detected (Table 4).…”
Section: Biogenic Aminesmentioning
confidence: 42%
“…Currently, MLF is considered as one of the most important factors that determine the presence of BAs in wines [62]. High concentrations (1-100 mg/L) of BAs can cause undesirable physiological effects in sensitive humans, especially when alcohol and acetaldehyde are present [55].…”
Section: Biogenic Aminesmentioning
confidence: 99%
“…For example, Varela et al [55] showed an increase in the concentration of some higher alcohols and esters in wines produced with autochthonous yeasts compared to the wines produced with commercial yeasts. Moreover, some non-Saccharomyces yeast may increase the concentration of biogenic amines in wines [56].…”
Section: Non-saccharomyces and Saccharomyces Co-inoculation Vs Sequementioning
confidence: 99%
“…It has been known that indigenous lactic acid bacteria naturally present in grapes must initiate spontaneous malolactic fermentation in wine [5,6]. This could trigger the production of undesirable metabolites (such as volatile acids and biogenic amines), which lowers the sensory quality of wine and further induces safety concerns [7,8].…”
Section: Introductionmentioning
confidence: 99%